Oxytocin-dependent consolation behavior in rodents - Burkett, J. P. (Science, 2016)
Consolation behavior toward distressed others is common in humans and great apes, yet our ability to explore the biological mechanisms underlying this behavior is limited by its apparent absence in laboratory animals. Here, we provide empirical evidence that a rodent species, the highly social and monogamous prairie vole (Microtus ochrogaster), greatly increases partner-directed grooming toward familiar conspecifics (but not strangers) that have experienced an unobserved stressor, providing social buffering. Prairie voles also match the fear response, anxiety-related behaviors, and corticosterone increase of the stressed cagemate, suggesting an empathy mechanism. Exposure to the stressed cagemate increases activity in the anterior cingulate cortex, and oxytocin receptor antagonist infused into this region abolishes the partner-directed response, showing conserved neural mechanisms between prairie vole and human.